Successful simulation of airflow in the microenvironment of an assembly automation machine and its implication - Thongsri, Jatuporn; Khaokom, Adisorn (My University, 2014)
Today, the hard disk drive (HDD) industry is using assembly automation machine (AAM) to construct head stack assembly (HSA) from smaller parts. AAM needs to operate in a clean environment with very low particle counts. To achieve this end, fan filter Unit (FFU) is used to supply purified air into the environment by filtering out airborne particles from recirculating air. In this study, we investigated numerically the airflow induced by FFUs inside a microenvironment that houses an AAM in an HDD factory. The boundary conditions chosen for simulation were directly derived from the real ambient conditions in this HDD factory. We found that the FFUs not only filter out airborne particles from the air supplied into the microenvironment but also act as a particle blocker, pushing away the nearby particles in the air surrounding the openings of the microenvironment. The findings from this study can be applied to cases where other kinds of machinery need to be protected from airborne particles. © (2014) Trans Tech Publications, Switzerland.
Keywords: Airflow; Automation; Computational fluid dynamics; Fan filter unit; Hard disk drive; Microenvironment